Revised Prototype Limited Liability Company Act (The Business Lawyer, 2011)
The Revised Prototype Limited Liability Company Act Editorial Board (the RPLLCA Editorial Board) for the Revised Prototype Limited Liability Company Act (the Act) is the primary drafter of the Act. Once approved by the RPLLCA Editorial Board, the Act is submitted to the main editorial board (the LPUE Editorial Board) of the LLCs, Partnerships and Unincorporated Entities Committee (LPUE) for final non-substantive editing. Once edited and approved by the LPUE Editorial Board, the Act is then submitted to LPUE for a vote to either approve or disapprove the Act. The Act is not subject to review or approval by any other body within the American Bar Association, The RPLLCA Editorial Board in conjunction with LPUE will present programs on the Act at ABA meetings and other state bar meetings.